Вы находитесь на странице: 1из 115

# POLITEHNICA University of Bucharest Faculty of Aerospace Engineering

## CHAPTER 7 Laplace Transform (Cont)

S.l.dr.ing.mat. Alina Bogoi Differential Equations

Theorems
Linear Property Derivatives Integrals

Laplace Transform
Theorem Description

## L{ f (t)}= est f (t)dt = F(s)

0

L{af (t ) + bg (t )} = aF ( s ) + bG ( s )
L{f (n) (t)}= snF(s) sn1 f (0) L f (n1) (0) 1 L { f ( ) d } = F ( s ) 0 s

## First Shifting Property Second Shifting Property

Diff_Eq_12_2012/201 3

## L{eat f (t)}= F(s a) L{ f (t a)u(t a)}= easF(s)

Transfer function
Input x(t) Black-box system Output y(t)

Consider an input-output system from x(t) to y(t) whose dynamic model has the form:

## dn d n 1 dm y (t ) + a1 n 1 y (t ) + ... + an y (t ) = b0 m x(t ) + ... + bm x(t ) n dt dt dt

Assume all initial conditions are zero, we get the transfer function(TF) of the system as
3 Diff_Eq_12_2012/201 3

## Connection between the t- and s-domains

dn d n 1 dm y( t ) + a1 n 1 y( t ) + ... + an y( t ) = b0 m x( t ) + ... + bm x( t ) n dt dt dt

## The transfer function, G(s), is defined by:

s nY ( s ) + a1s n 1Y ( s ) + ... + anY ( s ) = b0 s m X ( s ) + ... + bm X ( s )

## s n + a1s n 1 + ... + an = 0 Characteristic Equation

Diff_Eq_12_2012/201 3

## Poles of G(s) Roots of the Characteristic Eq

Transfer function
Input x(t) Black-box system Output y(t)

x(t)

differential equation

y(t)

X(s)

transfer function

Y(s)

G(s)
Diff_Eq_12_2012/201 3

## Example 1. Find the transfer function of the RLC R L

Input u(t) Solution: 1) Writing the differential equation of the system according to physical law:

i(t)

uc(t) Output

## &&C (t ) + RCu &C (t ) + uC (t ) = u (t ) LCu

2) Assuming all initial conditions are zero and applying Laplace transform 2

LCs U c ( s ) + RCsU c ( s ) + U c ( s ) = U ( s )

3

## Properties of transfer function

The transfer function is defined only for a linear time-invariant system, not for nonlinear system. All initial conditions of the system are set to zero. The transfer function is independent of the input of the system.

Diff_Eq_12_2012/201 3

Transfer function
X ( s) = A s+a

x (t ) = Ae at

## Position of poles and zeros

j

-a

Diff_Eq_12_2012/201 3

Transfer function
A1 s + B1 X ( s) = ( s + a )2 + b2

## Time-domain impulse response

x (t ) = Ae at sin(bt + )

## Position of poles and zeros

j

-a

0
9

Diff_Eq_12_2012/201 3

Transfer function
A1 s + B1 X ( s) = 2 s + b2

## Time-domain impulse response

x (t ) = A sin(bt + )

## Position of poles and zeros

j

b
0 0 i

Diff_Eq_12_2012/201 3

10

Transfer function
X ( s) = A sa

x (t ) = Ae at

## Position of poles and zeros

j

0 a

Diff_Eq_12_2012/201 3

11

Transfer function
A1 s + B1 X ( s) = ( s a )2 + b2

## Time-domain dynamic response

x (t ) = Ae at sin(bt + )

## Position of poles and zeros

j

0 0 i

-a

Diff_Eq_12_2012/201 3

12

## Summary of pole position & system dynamics

Diff_Eq_12_2012/201 3

13

Characteristic equation
-obtained by setting the denominator polynomial of the transfer function to zero

s n + an 1s n 1 + L + a1s + a0 = 0
Note: stability of linear single-input, single-output systems is completely governed by the roots of the characteristics equation.

Diff_Eq_12_2012/201 3

14

Significance of poles
The nature and value of the poles determine whether the system is stable or instable, and the type of response The nature and value of any pole is classified as a function of its location in the plan defined by: the Real part and Imaginary part of the pole [or in other words the s-domain]

Im(s) Re(s)
Diff_Eq_12_2012/201 3

## Stability Criterion vs Pole Locations Im ( s )

Stable Unstable

Re ( s )
The locations of poles in s-domain determine Diff_Eq_12_2012/201 whether the system is stable or unstable. 3

## Stability Criterion based on the Pole Locations

A system is stable if all its poles have negative real parts (i.e., there are all strictly inside the left-side s-plane) and unstable otherwise
Note: This criterion is valid only if the system is
Diff_Eq_12_2012/201 3

## How to analyze and design a control system

r
Expected value

e -

Controller

Actuator

Disturbance

Plant

y
Controlled variable

Error

Sensor

## The first thing is to establish system model (mathematical model)

Diff_Eq_12_2012/201 3 18

Block diagram
The transfer function relationship

Y ( s ) = G ( s )U ( s )
can be graphically denoted through a block diagram.
U(s) G(s) Y(s)

Diff_Eq_12_2012/201 3

19

1 Connection in series
U(s) G1(s) X(s)

## Equivalent transform of block diagram

G2(s) Y(s)

U(s)
G (s) = ?

G(s)

Y(s)

Y ( s) G ( s) = = G1 ( s ) G2 ( s ) U (s) Diff_Eq_12_2012/201
3

20

2.Connection in parallel
U(s) G1(s) G2(s) Y1(s)
Y(S)

U(s)

+
Y2(s)

G(s) Y(s)

G (s) = ?

## Y (s) G(s) = = G1 (s) + G2 (s) U (s)

Diff_Eq_12_2012/201 3 21

3. Negative feedback
R(s)
_ U(s)

G(s) H(s)

## Transfer function of a negative feedback system:

Diff_Eq_12_2012/201 3

G(s) M (s) = 1 + G ( s) H ( s)

22

Three models
Differential equation Transfer function Frequency characteristic
Study time-domain response Transfer function Linear system study frequency-domain response

## Differential Frequency Laplace equation Fourier characteristic transform transform 23

Diff_Eq_12_2012/201 3

## CHAPTER 8 The Fourier Series The Fourier Transform

S.l.dr.ing.mat. Alina Bogoi Differential Equations

Content
Periodic Functions Fourier Series Complex Form of the Fourier Series Impulse

Diff_Eq_12_2012/201 3

## Odd and Even Functions

A function f(x) is said to be even if f ( x) = f ( x) A function f(x) is said to be odd if f ( x) = f ( x)
Diff_Eq_12_2012/201 3

## Odd and Even Functions

Even Function Odd Function

f ( x) = f ( x)
f(x)

f ( x) = f ( x)
f(x)

Diff_Eq_12_2012/201 3

## Odd and Even Functions

Property

L L

f ( x ) dx = 2 f ( x ) dx , if f ( x ) is even
0

f ( x ) dx = 0 , if

f ( x ) is odd

## The product of an even and an odd function is odd.

Diff_Eq_12_2012/201 3

Periodic Functions
A function f ( t ) is periodic if it is defined for all real

## and if there is some positive number (the lowest), T such that f t + T = f t .

()

Diff_Eq_12_2012/201 3

Example:
Find its period. t t f (t ) = cos + cos 3 4

Diff_Eq_12_2012/201 3

Example:
Find its period. t t f (t ) = cos + cos 3 4
f (t ) = f (t + T )
t t 1 1 cos + cos = cos (t + T ) + cos (t + T ) 3 4 3 4

## Fact: cos = cos( + 2m)

T = 2m 3 T = 2 n Diff_Eq_12_2012/201 4 3
T = 6 m T = 24 smallest T

T = 8 n

Example:
Find its period.

f (t ) = cos 1t + cos 2t
f (t ) = f (t + T )
cos 1t + cos 2t = cos 1 (t + T ) + cos 2 (t + T )

1T = 2m
2 Diff_Eq_12_2012/201 3

T = 2 n

1 m = 2 n

## 1 must be a 2 rational number

Example:
f (t ) = cos 10t + cos(10 + )t
Is this function a periodic one?
1 10 = 2 10 +

## not a rational number

Diff_Eq_12_2012/201 3

Diff_Eq_12_2012/201 3

Rectangular Pulse

Diff_Eq_12_2012/201 3

Sawtooth

wave

Diff_Eq_12_2012/201 3

Orthogonal Functions
Call a set of functions {k} orthogonal on an interval a < t < b if it satisfies

0 ( ) ( ) t t dt = m n a rn
b
Diff_Eq_12_2012/201 3

mn m=n

Define 0=2/T.

Prove!

## mn 0 T / 2 sin(m0t ) sin(n0t )dt = T / 2 m = n

T /2

T /2

Diff_Eq_12_2012/201 T /2 3

## sin mx cos nxdx = 0

Diff_Eq_12_2012/201 3

Fourier Series
A Fourier series is an expansion of a periodic function f (t) in terms of an infinite sum of cosines and sines

## a0 f (t ) = + (an cos nt + bn sin nt ) 2 n =1

Diff_Eq_12_2012/201 3

Dirichlet Conditions
A periodic function(signal) f(t), has a Fourier series if it satisfies the following conditions: 1. f(t) is absolutely integrable over any period, namely
a +T

| f (t ) | dt < ,
a

a R

2. f(t) has only a finite number of maxima and minima over any period 3. f(t) has only a finite number of discontinuities over any period
Diff_Eq_12_2012/201 3

Harmonics
2 0 = 2f 0 = T
Define

n = n0 ,

## a0 f (t ) = + an cos n0t + bn sin n0t 2 n =1 n =1

a0 f (t ) = + an cos nt + bn sin n t 2 n =1 n =1 Diff_Eq_12_2012/201
3

f(t)

Periodic Function

a0 2

=
t

a1 cos t

b1 sin t

+
a2 cos 2t

+
b2 sin 2t

+
Diff_Eq_12_2012/201 3

## a0 f (t ) = + (an cos nt + bn sin nt ) 2 n =1 2 = Fundemental angular frequency where =

T
2 a0 = f (t )dt T 0 2 an = f (t ) cos ntdt T 0
T T

2 bn = f (t ) sin ntdt T 0
T /2 T / 2

## *we can also use the integrals limit

Diff_Eq_12_2012/201 3

Example 1
Determine the Fourier series representation of the following waveform.

Diff_Eq_12_2012/201 3

Solution
First, determine the period & describe the one period of the function:

T=2

Diff_Eq_12_2012/201 3

## 1, 0 < t < 1 f (t ) = 0, 1 < t < 2

f (t + 2) = f (t )

## 2 2 a0 = f (t )dt = f (t )dt = 1dt + 0dt = 1 0 = 1 T 0 20 0 1

2 sin n sin n t an = f (t ) cos ntdt = 1cos n tdt + 0dt = = =0 T 0 n n 0 0 1
2 1 2 1

## 2 cos n t 1 cos n = bn = f (t ) sin ntdt = 1sin n tdt + 0dt = T 0 n 0 n 0 1

2 1 2

1 (1) n 2 / n bn = = n 0
Diff_Eq_12_2012/201 3

n odd

, n even

Finally,

## a0 f (t ) = + (an cos nt + bn sin nt ) 2 n =1

n 1 1 (1) = + sin nt 2 n =1 n 2 1 2 2 = + sin t + sin 3t + sin 5t + K 5 2 3

Diff_Eq_12_2012/201 3

(a)
2 sin t

(b)
2 sin t + 2 sin 3t 3

(c)

(d)

sin t +

2 2 sin 3t + sin 5t 3 5

sin t +

## 2 2 2 sin 3t + sin 5t + sin 7t 3 5 7

Diff_Eq_12_2012/201 3

(e)

sin t +

(f)

## 1 2 2 2 + sin t + sin 3t + K + sin 23t 2 3 23 Diff_Eq_12_2012/201

3

Example 2
Given

f (t) = t, 1 t 1
f (t + 2) = f (t )

Sketch the graph of f (t) such that 3 t 3. Then compute the Fourier series expansion of f (t).

Diff_Eq_12_2012/201 3

Solution
The function is described by the following graph:

3

T=2

## Then we compute the coefficients:

t 2 2 1 1 a0 = f (t )dt = tdt = = =0 2 1 2 T 1 2 1
1 1 2

## 2 an = f (t ) cos ntdt = t cos n tdt = 0 T 1 1

2 2 cos n 2(1) bn = f (t ) sin ntdt = = T 1 n n
1
Diff_Eq_12_2012/201 3

n +1

Finally,

## a0 f (t ) = + (an cos nt + bn sin nt ) 2 n =1 2(1) n +1 = sin nt n n =1 2 2 2 = sin t sin 2t + sin 3t K 2 3

Diff_Eq_12_2012/201 3

Example 3(homework)
2 t , 0 < t < 2 Given v(t ) = , 2<t <4 0
v(t + 4) = v(t )

Sketch the graph of v (t) such that 0 t 12. Then compute the Fourier series expansion of v (t).

Diff_Eq_12_2012/201 3

Solution
The function is described by the following graph:
v (t) 2 0 2 T=4 4 6 8 10 12 t

3

Finally,

## a0 v(t ) = + (an cos nt + bn sin nt ) 2 n =1 1 2[1 (1) n ] nt 2 nt = + cos sin + 2 2 2 n =1 n 2 n 2

Diff_Eq_12_2012/201 3

## Fourier Coefficients of Even Functions

f (t ) = f (t )
a0 f (t ) = + an cos nt 2 n =1
Diff_Eq_12_2012/201 3

4 T /2 an = f (t ) cos(nt )dt T 0

## Fourier Coefficients of Odd Functions

f (t ) = f (t )
f (t ) = bn sin nt
n =1

Diff_Eq_12_2012/201 3

4 T /2 bn = f (t ) sin(nt )dt T 0

Example 4
Given
1 , 2 < t < 1 f (t ) = t , 1 < t < 1 1 , 1< t < 2

f (t + 4) = f (t )

Sketch the graph of f (t) such that 6 t 6. Then compute the Fourier series expansion of f (t).

Diff_Eq_12_2012/201 3

Solution
The function is described by the following graph:
f (t) 1 6 4 2 1 0 2 4 6 t

T=4

3

## Then we compute the coefficients. Since f (t) is an odd function, then

2 a0 = f (t )dt = 0 T 2
and
2

2 an = f (t ) cos ntdt = 0 T 2

## 4 2 cos n bn = f (t ) sin ntdt = T 0 n

Diff_Eq_12_2012/201 3

Finally,

## a0 f (t ) = + (an cos nt + bn sin nt ) 2 n =1 nt 2 cos n = sin n 2 n =1 nt (1) n +1 = 2 sin n 2 n =1

Diff_Eq_12_2012/201 3

Example 5
Compute the Fourier series expansion of f (t).

Diff_Eq_12_2012/201 3

Solution
The function is described by
1 , 0 < t < 1 f (t ) = 2 , 1 < t < 2 1 , 2 < t < 3
T=3

f (t + 3) = f (t )

T=3

and

2 2 = = 3 T

Diff_Eq_12_2012/201 3

## Or, since f (t) is an even function, then

2 4 a0 = f (t )dt = T 0 T

3/ 2

8 f (t )dt = 3

bn = 0

4 an = T

3/ 2

## 2 2n f (t ) cos ntdt = sin n 3

4 2 1 2n f (t ) = sin 3 n =1 n 3
Diff_Eq_12_2012/201 3

2n t cos 3

Example 6
Compute the Fourier sine series expansion of an odd f (t), where
f (t ) = 1 , 0 < t < f (t ) = 1 , < t < 0

Diff_Eq_12_2012/201 3

Solution
Since we want to seek the half-range sine series, the function to is extended to be an odd function:
f (t) 1 0 t 2 f (t) 1 0 1 T = 2 2 t

2 = =1 T
Diff_Eq_12_2012/201 3

## Hence, the coefficients are

a0 = a n = 0
and

4 bn = T
Therefore,

T /2

4 / n f (t ) sin ntdt = 0

, n odd , n even

2 f (t ) = (1 cos n ) sin nt = n =1 n
Diff_Eq_12_2012/201 3

n odd

4 sin nt n =1 n

Example 7
Determine the half-range cosine series expansion of the function
f (t ) = 2t 1 , 0 < t < 1

Sketch the graphs of both f (t) and the periodic function represented by the series expansion for 3 < t < 3.

Diff_Eq_12_2012/201 3

Solution
Since we want to seek the half-range cosine series, the function to is extended to be an even function:
f (t)
1 1
1 2

f (t)
1 1

2
3

2 1 1
T=2

2 = = T
Diff_Eq_12_2012/201 3

Therefore,

f (t ) = a0 + an cos nt
n =1

8 8 = 0 + 2 2 cos nt = 2 n n =1
n odd

n odd

1 cos nt 2 n =1 n

Diff_Eq_12_2012/201 3

## The Complex Form of Fourier Series

f ( ) = a0 / 2 + an cos n + bn sin n
n =1 n =1

## Let us utilize the Euler formulae.

e +e cos = 2
e e sin = 2i
i

T = 2

=1

Diff_Eq_12_2012/201 3

## an cos n + bn sin n an jbn jn an + jbn jn = e e + 2 2

Denoting

a n jbn cn = 2
and

cn

a n + jbn = 2

c0 = a0 / 2

Diff_Eq_12_2012/201 3

an cos n + bn sin n = cn e
jn

+ c n e

jn

Diff_Eq_12_2012/201 3

## The Fourier series for can be expressed as:

f ( )
in in

f ( ) = c0 + cn e
n =1

+ c n e

n =

ce
n

in

Diff_Eq_12_2012/201 3

## The coefficients can be evaluated in the following manner.

an ibn cn = 2 1 i f ( ) cos n d = 2 2

f ( ) sin n d

1 = f ( )( cos n i sin n )d 2 1 in = f ( ) e d 2
Diff_Eq_12_2012/201 3

Identically

an + ibn 1 in = f e d c n = ( ) 2 2 1 in cn = f e d ( ) 2
.

n = 0 , 1, 2 , L
Diff_Eq_12_2012/201 3

## The complex form of the Fourier series of

f ( ) with period

is:

f ( ) =

n =

ce
n

in

Diff_Eq_12_2012/201 3

## Complex Frequency Spectra

* cn =| cn | ejn , cn =cn =| cn | ejn

1 2 2 | cn |=| cn |= an +bn 2 1 c0 = a0 2

bn n = 1 , 2 , 3 , L n =tan a n
1

|cn|

amplitude spectrum

n
Diff_Eq_12_2012/201 3

phase spectrum

Example 8
Obtain the complex Fourier series of the following function f (t )
e 2
f (t )= e
t

1
4 2 0 2 4

Diff_Eq_12_2012/201 3

Solution
Since T = 2 , = 1 . Hence

1 c0 = T

f (t )dt
0 2

1 = 2

e dt
t 0 2 0

1 t = e 2

[ ]

e 2 1 = 2

Diff_Eq_12_2012/201 3

1 cn = T

f (t )e int dt
2

1 = 2 1 = 2

ee
0

t int

1 dt = 2
2

e
0

(1in ) t

dt

e 1 in 0
(1in ) t

## e 2 (1in ) 1 e 2 e i 2 n 1 e 2 1 = = = 2 (1 in) 2 (1 in) 2 (1 in)

i 2 n Diff_Eq_12_2012/201 since e = cos 2n i sin 2n = 1 0 = 1 3

cn

n =0

1 e 1 = = = c0 2 (1 in) n =0 2 e

## Therefore, the complex Fourier series of f (t) is

f (t ) =

n =

ce
n

int

1 int = e n = 2 (1 in)

Diff_Eq_12_2012/201 3

## cn is a complex term, and it depends on n. Therefore, we may plot a graph of |cn| vs n.

cn =

2 1 + n 2

In other words, we have transformed the function f (t) in the time domain (t), to the function cn in the Diff_Eq_12_2012/201 frequency domain (n).
3

Example 9
Obtain the complex Fourier series of the function in Example 1.

Diff_Eq_12_2012/201 3

=
1 c0 = T
T

Solution

1 1 f (t )dt = 1dt = 20 2
int

1 cn = T

f (t )e
0 in t

1 dt = 1e in t dt + 0 20 1

1 e j in (e 1) = = 2 in 0 2n
Diff_Eq_12_2012/201 3

But

## *Here notice that cn n =0 c0 . Therefore,

Diff_Eq_12_2012/201 3

f (t ) =

n =

ce
n

int

1 i in t = e 2 n = n
n0 n odd

## The plot of |cn| vs n is shown below

1 c0 = 2

1 , n odd c n = n 0, n even
0.5

Diff_Eq_12_2012/201 3

Synthesis
a0 2nt 2nt f (t ) = + an cos + bn sin T T 2 n =1 n =1
DC Part Even Part Odd Part

## T is a period of all the above signals

Let 0=2/T.
a0 f (t ) = + an cos(n0t ) + bn sin( n0t ) Diff_Eq_12_2012/2012 n =1 n =1 3

Decomposition
a0 f (t ) = + an cos(n0t ) + bn sin( n0t ) 2 n =1 n =1

## 2 t 0 +T a0 = f (t )dt t T 0 2 t 0 +T an = f (t ) cos n0tdt T t0 2 t 0 +T bn = f (t ) sin n0tdt t T 0 Diff_Eq_12_2012/201

3

n = 1,2, L n = 1,2, L

f(t)
1

-6 -5 -4 -3 -2 -

2 3

4 5

## 1 1 2 1 f (t ) = + sin t + sin 3t + sin 5t + L 5 2 3

Diff_Eq_12_2012/201 3

Harmonics
a0 f (t ) = + an cos nt + bn sin nt 2 n =1 n =1

a0 a b 2 2 n n = + an + bn cos nt + sin n t 2 2 a2 + b2 2 n =1 + a b n n n n

## a0 2 2 = + an + bn (cos n cos nt + sin n sin nt ) 2 n =1

Diff_Eq_12_2012/201 3

## Amplitudes and Phase Angles

f (t ) = C0 + Cn cos(nt n )
n =1

harmonic amplitude

phase angle

a0 C0 = 2
Diff_Eq_12_2012/201 3

2 2 C n = an + bn

bn n = tan a n
1

## The Fourier Transform

Introduction
Fourier transform is another method to transform a signal from time domain to frequency domain The basic idea of Fourier transform comes from the complex Fourier series Practically, many signals are non-periodic Fourier transform use the principal of the Fourier series, with assumption that the period of the non-periodic signal is infinity (T ). Diff_Eq_12_2012/201
3

## Recall the complex form of Fourier series:

f (t ) =
n =

c e
n

jn0t

(2.1)

where

1 jn0t cn = f (t )e dt T T / 2

T /2

(2.2)

## Substituting (2.2) into (2.1) gives

jn0t 1 T /2 jn0t f (t ) = f (t )e dt e n = T T / 2 Diff_Eq_12_2012/201

(2.3)

## Fourier transform-different forms

[ g ( t )] = g ( t ) e jt dt = G ( j )

[G ( )] = 1 2
1

G ( j ) e jt d = g ( t )

jt 1 [ g ( t ) ] = g t e dt = G ( ) ( ) 2 jt 1 [G ( )] = G e d = g ( t ) ( ) 2 1

[ g ( t )] = g ( t ) e j 2 ft dt = G ( f )

[G ( f )] = G ( f ) e j 2 ft d = g ( t )

A physical process can be described either in the time domain by a function of time t, g(t), or in the frequency domain as a function of frequency f, G(f). g(t) and G(f) are two different representations of the same process.

Diff_Eq_12_2012/201 3

Fourier Series:
f (t ) =
n = jn0t c e n

## Period Function Discrete Spectra Non-Period Function

1 cn = T

T /2

T / 2

f (t )e jn0t dt

Fourier Integral:

1 jt f (t ) = F ( j ) e d 2
F ( j) = f (t )e jt dt

Diff_Eq_12_2012/201 3

Continuous Spectra

Therefore
1 f (t ) = 2

F ( j )e j t d

where

F ( j ) =

f (t )e j t d

We say that F(j) is the Fourier transform of f (t), and f (t) is the inverse Fourier transform of F(j)
Diff_Eq_12_2012/201 3

Or in mathematical expression,
F ( ) = F { f (t )} =

f (t )e jt d

and

1 f (t ) = F {F ( )} = 2
1

F ( )e

jt

where F and F 1 is the Fourier transform and inverse Fourier transform operator respectively:
Diff_Eq_12_2012/201 3

f (t )

F 1

F ( )

## Fourier Transform Pair

Inverse Fourier Transform:

1 jt f (t ) = F ( j)e d 2
Fourier Transform:

Synthesis

F ( j) = f (t )e

Diff_Eq_12_2012/201 3

j t

dt

Analysis

Generally, the Fourier transform F(j) exists when the Fourier integral converges A condition for a function f(t) to have a Fourier transform is, f(t) can be completely integrable, i.e.

f (t ) dt <

## This condition is sufficient but not necessary

Diff_Eq_12_2012/201 3

## Existence of the Fourier Transform

Sufficient Condition: f(t) is absolutely integrable, i.e.,

Diff_Eq_12_2012/201 3

| f (t ) |dt <

Continuous Spectra
F ( j) = f (t )e jt dt

F ( j) = FR ( j) + jFI ( j)

FI(j)

=| F ( j) | e
Diff_Eq_12_2012/201 3

j ( )
Phase

| ) j |F( ()

FR(j)

Magnitude

Example
1

f(t)
1

-1

t
1

F ( j) = f (t )e

j t

dt = e
1

jt

1 jt e dt = j

2 sin j j j = (e e ) = Diff_Eq_12_2012/201
3

Example
F( ) F( ) 33 22 11 00 -10 -10 -5 -5 00 55 10 10

f(-1 t-1 )
33 |F( )| |F( )| 22 11

-1

1
-5 -5 00 55

t
jt

arg[F( )] arg[F( )]

F ( j) = f (t )e

j t

dt = e
1
22

00 -10 -10 1 44

1 j t e dt = j
10 10 00 55 10 10

## 2 sin j j j 00 = (e e ) = -10 -5 -10 -5 Diff_Eq_12_2012/201

3

Example
f(t)

et
t

F ( j) = f (t )e

0 Diff_Eq_12_2012/201 3

j t

dt = e t e jt dt
0

= e

( + j ) t

1 dt = + j

Example
f(t)
1 1 |F(j)| |F(j )| =2 =2 0.5 0.5

et
0 0 5 5

0 0

-10 -10

-5 -5

t 10 10

arg[F(j)] arg[F(j )]

F ( j) = f (t )e
0 Diff_Eq_12_2012/201 3

2 2

j t

0 0

dt = e t e jt dt
0
-5 -5 0 0 5 5 10 10

= e

( + j ) t

-2 -2

1 dt = + j
-10 -10

## Comparison between Fourier series and Fourier transform

Fourier series Support periodic function

Fourier transform

## Discrete frequency spectrum

Diff_Eq_12_2012/201 3

Example 1
Using the definition, find the Fourier transform of (t). Then deduce the Fourier transform of 1.

## *Recall the sifting property:

(t a) f (t )dt = f (a)

## The Fourier transform of f (t) = (t) is

F () = F{ (t)} = (t)e jt dt = e j0 = e0 = 1
Diff_Eq_12_2012/201 3

Principle of duality
The definition of Fourier transform is
F ( j ) = F { f (t )} =

f (t )e j t d

(2.4)

## and the inverse Fourier transform is

1 1 f (t ) = F {F ( j )} = 2

F ( j )e j t d

(2.5)

Note that the function f (t) and its transform F(j) can be derived from each Diff_Eq_12_2012/201 3 other

From (2.5),
1 f (t ) = 2

F ( j )e j t d

If we interchange t and
1 f ( ) = 2 1 f ( ) = 2
Diff_Eq_12_2012/201 3

F ( jt)e
j t

j t

dt

## And replace with

F( jt)e

1 dt = F {F ( jt )} 2

or

F {F ( jt )} = 2 f ( )

## For example, using integration, the Fourier transform of 1 is

j + j e e e F {1} = 1e jt dt = =? = j j jt

At first, we may conclude that 1 has no Fourier transform, but in fact, it can be found using the principle of duality!

Diff_Eq_12_2012/201 3

Solution
The Fourier transform of f (t) = (t) is

F () = F{ (t)} = (t)e jt dt = e j0 = e0 = 1

Then, using the duality principle, the Fourier transform of 1 is F {1} = 2f ( ) = 2 ( ) = 2 ( ) since ( ) = ( ).
Diff_Eq_12_2012/201 3